Multimode instabilities in mid-infrared quantum cascade lasers - Bugajski, Maciej; Pierściński, Kamil; Pierscinska, Dorota; Szerling, Anna; Kosiel, Kamil (Photonics Letters of Poland, 2013)
We present experimental evidence for mid-infrared frequency comb based on AlGaAs/GaAs quantum cascade laser. The comb-like emission spectra span over 50 cm-1 at a center wavenumber 1080 cm-1. The measured width of the comb lines is < 20 MHz. The instability sets in when the intracavity power is sufficiently large. In addition, intersubband transitions feature strong third-order optical nonlinearities chi(3), due to the large matrix element between the upper and lower laser states, allowing parametric process due to four-wave mixing. The observed spectral behavior is similar in many ways to the Risken-Nummedal-Graham-Haken (RNGH) instability. Full Text: PDF References H. Risken, K. Nummedal, "Self-Pulsing in Lasers", J. Appl. Phys. 39, 4662 (1968). CrossRef P. Graham, H. Haken, "Quantum theory of light propagation in a fluctuating laser-active medium", Z. Phys. 213, 420 (1968). CrossRef E. M. Pessina, G. Bonfrate, F. Fontana, L. A. Lugiato, "Experimental observation of the Risken-Nummedal-Graham-Haken multimode laser instability", Phys. Rev. A 56, 4086 (1997). CrossRef L. Allen and J. H. Eberly, Optical Resonance and Two Level Atoms (Dover, New York, 1987). R. W. Boyd, Nonlinear Optics, 2nd ed. (Academic Press, London, 2003). R. Paiella et al., "Self-Mode-Locking of Quantum Cascade Lasers with Giant Ultrafast Optical Nonlinearities", Science 290, 1739 (2000). CrossRef A. Soibel, F. Capasso, C. Gmachl, M. L. Peabody, A. M. Sergent, R. Paiella, D. L. Sivco, A. Y. Cho, H. C. Liu, "Stability of pulse emission and enhancement of intracavity second-harmonic generation in self-mode-locked quantum cascade lasers", IEEE J. Quantum Electron. 40, 197 (2004). CrossRef D. J. Derickson, at al., "Short pulse generation using multisegment mode-locked semiconductor lasers ", IEEE J. Quantum Electron. 28, 2186 (1992). CrossRef C. Y. Wang et al., "Mode-locked pulses from mid-infrared Quantum Cascade Lasers", Opt. Express 17, 12929 (2009). CrossRef A. Gordon et al., "Multimode regimes in quantum cascade lasers: From coherent instabilities to spatial hole burning", Phys. Rev. A 77, 053804 (2008). CrossRef T. Udern, R. Holzwarth, T. W. Hansch, "Review article Optical frequency metrology", Nature 416, 233 (2002). CrossRef A. Hugi, G. Villares, S. Blaser, H. C. Liu, J. Faist, "Mid-infrared frequency comb based on a quantum cascade laser", Nature 492, 229 (2012). CrossRef K. Kosiel, M. Bugajski, A. Szerling et al., "77 K operation of AlGaAs quantum cascade laser at 9um", Photonics Letters of Poland 1, 16 (2009) DirectLink K. Kosiel, J. Kubacka-Traczyk, P. Karbownik, A. Szerling, J. Muszalski, M. Bugajski, P. Romanowski, J.Gaca, M. Wójcik, "Molecular-beam epitaxy growth and characterization of mid-infrared quantum cascade laser structures", Microelectronics Journal, 40, 565 (2009) CrossRef K. Kosiel, M. Bugajski, A. Szerling et al., "Room temperature AlGaAs/GaAs quantum cascade lasers", Photonics Letters of Poland 3, 55 (2011) DirectLink M. Bugajski et al., "High performance GaAs/AlGaAs quantum cascade lasers: optimization of electrical and thermal properties", Proc. of SPIE Vol. 8432, 84320I (2012) CrossRef K. Pierściński, D. Pierścińska, M. Iwińska, K. Kosiel, A. Szerling, P. Karbownik, M. Bugajski, "Investigation of thermal properties of mid-infrared AlGaAs/GaAs quantum cascade lasers ", J. Appl. Phys. 112, 043112 (2012) CrossRef C. Y. Wang et al., "Coherent instabilities in a semiconductor laser with fast gain recovery", Phys. Rev. A 75, 031802 (2007) CrossRef D. Walrod, S. Y. Auyang, P. A. Wolf, M. Sugimoto, "Observation of third order optical nonlinearity due to intersubband transitions in AlGaAs/GaAs superlattices", Appl. Phys. Lett. 59, 2932 (1991). CrossRef H. Choi, V-M. Gkortsas, L. Diehl et al., "Ultrafast Rabi flopping and coherent pulse propagation in a quantum cascade laser", Nature Photonics CrossRef